PENGARUH PROFITABILITAS, PEMBIAYAAN, LIKUIDITAS SAHAM DAN RISIKO SISTEMATIK (BETA) TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - Yusanto Ahmad, - (2013)
Capital market as the medium for mobilization fund that stem from society to various of sectors that execute investment. Main requirement was desired by investors to ready channeled its fund pass by capital market id safeness of its investment. Getting the return (advantage) is main purpose from commerce of activity investors in capital market. The objective of this research to analyze the influence of Profitability (proxied by Return on Asset/ROA), Finance (proxied by Debt to Asset RatioDAR), Liquidity Stock and Beta to stock Return of company that listed in Indonesia Stock Exchange at 2012. As the sample used purposive sampling with criteria as : The company that listed in Indonesian Stock Exchange at 2012, the stock of company getting return seven working days after the published financial statement and the company makes a profit. The number of population for this research is 482 company and the number of sample that examine after passed the purposive sampling phase is 73 company. Analyze techniqueto use in this research is multiple linear regression to obtain picture which totally regarding relationship between one variable with other variable. The result of this research shows that Return on Asset (ROA) variables and Stock Likuidity variables has significant influence to stock return, while Debt to Asset Ratios (DAR) variables and Beta variables has not significant influence to stock return. While, four independent variable (ROA, DAR, Stock Liquidity and Beta) is simultaneosly does have a significant influence to stock prices with the significant value is smaller than 0.05 or equal to 0.001. The result which not significant from DAR and Beta variable cannot be made as the reference in determaining investment strategy for investor inculcating its share in capital market.